(3aj GdTQGFWs - (3eLghds
(3ChdgG (B:s
(3HSe Gddg (B.. (3Gdbhd aj GdTQGFW hgh CQHYI , GdGhd aj TQGFW Gdhba hgh CQHYI GdJfLjQ hGdOhGe (B.. (3ajgG hEf GdKGfj TQW aj GdLedI (B.. (3GdJbjjO Edi GdReGf eVQ Cj GdOhGe hTQW HYHGQI CNQi dGHO aj Gdhba HeOM eG jfGaj GdOhGe (B...s
(3BNQgG (B:s
... (3Ef Gdjejf HefdI GdEbQGQ ef MjK GdEdRGe hGdGdJRGe Hbg aj Mda dce HGddg aUObhg aEf GdJUOjb dG jajO CRjO efg Pdc haSQ CfgG HefRdI GdHjfI ef MjK GdEKHGJ (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis